Multiple sexually transmitted co-infections are associated with adverse reproductive outcomes in asymptomatic adolescent pregnant women; A Prospective cohort study - Wasnik, Kirti; Mittal, Pratima; Ghope, Priti; Sonkar, Subash C.; Arora, Geetika; Saluja, Daman (Frontiers in Medicine, 2022)
Background A prospective cohort was conducted to assess the prevalence of seven RTIs/STIs in adolescent asymptomatic pregnant women to find a significant correlation between infection and pregnancy. Methods The study was restricted to 18–19 years of asymptomatic adolescent pregnant women attending Ante-Natal Care and the health status of the pregnant women were followed up to parturition. The health status of the infant was followed till 6 months post-delivery. The prevalence of the concerning pathogens and the significance of their association with adverse outcomes of pregnancy were determined. Results Among 279 subjects, the most significant co-infections were observed for M. hominis with U. parvum (9.31%; p-value–0.0071/OR−2.6421) and U. urealyticum (7.88%; p-value–0.0119/OR−2.6455). Statistically significant associations were found between C. trachomatis [(p-value-0.0439); OR−2.9902] and M. genitalium [(p-value−0.0284); OR−3.442] with PTB, N. gonorrhoeae with LBW <2.5 kg [(p-value−0.0052);OR−4.9017], U. urealyticum with VLBW <2 kg [(p-value-0.0262);OR−3.0207], M. genitalium [(p-value-0.0184); OR−11.7976] and T. vaginalis with PROM [(p-value 0.0063); OR−19.4275] while M. genitalium [(p-value 0.0190); OR–12.9230] and U. urealyticum [(p-value 0.0063); OR-14.5149] with PPROM with 95% CI respectively. Conclusions Asymptomatic adolescents are at high risk of adverse pregnancy outcomes if infected with the concerned pathogens.